(untitled) (mathematica didactica, 2025)
Mathematics is fundamental to many fields of study, both within and outside STEM. However, many students are not aware of this fact: They often start their studies with wrong or insufficient perceptions about the mathematical requirements for their studies. First-year students’ perceptions of the mathematical requirements of different subjects are formed before they start their studies, and teaching and teachers have a significant influence on them. The aim of this article is therefore to examine teachers’ perceptions of general and subject-specific mathematical requirements in selected examples of subjects.